The Mitochondrial Genome in Nematode Phylogenetics - Kern, Elizabeth M. A.; Kim, Taeho; Park, Joong-Ki (Frontiers in Ecology and Evolution, 2020)
In recent decades, great strides have been made using various kinds of data including molecular sequences to clarify the phylogenetic relationships of nematodes. Although SSU rDNA sequences are among the most widely used markers in nematode phylogeny, there are areas within Nematoda that do not seem amenable to resolution by this single nuclear gene. The use of the complete mitochondrial genome (mitogenome) is an alternative and powerful molecular method for inferring phylogenies and is frequently used in nematodes. Here we present an overview of the contributions of mitogenome phylogenies in the phylum Nematoda. The nematode mitogenome has several practical strengths as a phylogenetic marker, and has yielded well-supported results for clades which were not well resolved using other approaches. We discuss places where nematode mitogenomes have sometimes produced alternative tree topologies compared to nuclear gene phylogenies, review to what extent mitochondrial gene order is useful in nematode phylogenetics, and make recommendations for promising future areas of research.